The challenges of large-scale curriculum development: A case study of Guyana and St. Kitts and Nevis - Gregory Rodney MacKinnon; Susan Sarah Owen; Tyler MacLean; Rajkumar Sookraj (Universitas Pendidikan Indonesia, 2023)
Guyana and St. Kitts and Nevis have recently and independently undertaken large-scale enhancement of their public-school curriculum. An educational leadership consultancy has led the process using an implementation model based on feedback from country communities regarding graduation outcomes and the ensuing preparation of a Curriculum and Assessment Framework. Curriculum outcomes were based on international best practices and captured in a curriculum template premised on backward design. Using a mixed methods approach, independent researchers analyzed factors that necessarily impact the process of curriculum development. Quantitative and qualitative research feedback established challenges in the process of curriculum development. Categories of feedback arose from surveys, interviews, and focus groups. These included challenges in preparation for writing, perceived impact on the school system, and working conditions during the process of writing. Similarities and differences in the country contexts are examined and suggestions for an improved approach are recommended. Abstrak Guyana dan St. Kitts dan Nevis baru-baru ini dan secara mandiri melakukan peningkatan besar-besaran kurikulum sekolah umum mereka. Konsultan kepemimpinan pendidikan telah memimpin proses dalam implementasi model berdasarkan umpan balik dari komunitas negara mengenai hasil kelulusan dan persiapan Kurikulum dan Kerangka Penilaian selanjutnya. Hasil kurikulum didasarkan pada praktik terbaik internasional dan diimplementasikan dalam templat kurikulum yang didasarkan pada desain mundur. Dengan menggunakan pendekatan metode campuran, peneliti menganalisis faktor-faktor yang memengaruhi proses pengembangan kurikulum. Penelitian kuantitatif dan kualitatif membentuk tantangan dalam proses pengembangan kurikulum. Kategori umpan balik muncul dari survei, wawancara, dan kelompok fokus. Termasuk tantangan dalam persiapan menulis, dampak yang dirasakan pada sistem sekolah dan kondisi kerja selama proses penulisan. Kemiripan dan perbedaan dalam konteks negara diperiksa dan saran untuk pendekatan yang lebih baik direkomendasikan. Kata Kunci: framework kurikulum dan asesmen; pengembangan kurikulum; tantangan kurikulum